An integrated network management approach for managing hybrid IP and WDM networks. - Raptis, L. (IEEE Network : the magazine of global information exchange)
Pacing toward converged voice and data networks, the IP over WDM/OTN network architecture supported by MPLS satisfies the advanced next-generation network requirements to provide fast, reliable and flexible connectivity services. Acknowledging the advantages of networks that utilize the above technologies, operators evolve their networks in that direction, while continuously working to provide new services to attract customers. In their effort to facilitate such services in a flexible and cost-effective way, an integrated network management system for IP and WDM technologies is a prerequisite. This article proposes a management architecture that provides for this integration. Different approaches to integrating multilayer networks are briefly described covering both the control and management planes. The adopted solution is based mainly on the management plane utilizing the control plane wherever possible. Additionally, preliminary results from the evaluation of the configuration management functionality of the proposed system in a testbed environment are presented, concluding with future extensions that also cover fault and performance management.